(untitled) (Western European Journal of Medicine and Medical Science, 2024)
Atopic dermatitis in children is a chronic inflammatory skin disease accompanied by severe itching, rashes and redness. According to WHO ATd suffers from 15 to 32% of children. It develops in the first year of a child’s life, can persist in adults. The risk factor is genetic predisposition and food allergy. Atopic dermatitis is accompanied by both physical and psychological symptoms, which are aggravated by stress and contact with allergens. The dust factor can also provoke the development of relapses.